Steroid treatment in the management of destructive thyrotoxicosis induced by PD1 blockade. Issue 4 (29th June 2022) - Brancatella, Alessandro; Pierotti, Laura; Viola, Nicola; Lupi, Isabella; Montanelli, Lucia; Cremolini, Chiara; Piaggi, Paolo; Chella, Antonio; Antonuzzo, Andrea; Sgrò, Daniele; Antonangeli, Lucia; Sardella, Chiara; et al.
Abstract : Objective: Destructive thyroiditis is the most common endocrine immune-related adverse event (iRAEs) in patients treated with anti-PD1/PD-L1 agents. Given its self-limited course, current guidelines recommend no treatment for this iRAE. Nevertheless, in patients with enlarged thyroid volume and a poor performance status, thyrotoxicosis may be particularly severe and harmful. The aim of the study is to evaluate if steroid treatment might be useful in improving thyrotoxicosis in subjects with a poor performance status. Methods: We conducted a retrospective study, comparing the course of thyrotoxicosis of four patients treated with oral prednisone at the dosage of 25 mg/day (tapered to discontinuation in 3 weeks) and an enlarged thyroid volume to that of eight patients with similar thyroid volume who were left untreated. Results: The levels of thyroid hormones were lower in subjects treated compared to those untreated at time of 7, 14, 21, 28, 35, 42, 60 and 90 days ( P < 0.05 at each time). The time to remission of thyrotoxicosis was 24 days in patients treated with steroids and 120 days in untreated patients ( P < 0.001). At 6 months, the rate of evolution to hypothyroidism was similar in the two groups (4/4 in the steroid group vs 7/8 in the untreated group, P = 0.74) and no difference was found in tumor progression ( P = 0.89). Conclusions: Our preliminary data suggest that in patients with a poor performance status experiencing a severe destructive thyrotoxicosis induced by PD-1 blockade, a short period of administration of oral prednisone is effective in obtaining a quick reduction of the levels of thyroid hormones.